Polycyclic aromatic hydrocarbons and their nitro derivatives from indoor biomass-fueled cooking in two rural areas of Thailand: a case study - Orakij W. (2017)
© 2017, Springer Science+Business Media Dordrecht. Household fuel combustion for cooking is a major source of hazardous pollutants, including polycyclic aromatic hydrocarbons (PAHs) and their nitro derivatives (NPAHs). These pollutants impact indoor air quality and human health. In this study of two rural households in Chiang Mai, Thailand, PM 2.5 samples were collected both inside and outside the houses during cooking and noncooking periods. Real-time monitoring of indoor PM 2.5 was also conducted. The concentrations of PAHs, NPAHs, levoglucosan (LG), and carbon fractions in the PM 2.5 fractions were quantified. The most severe contamination was observed inside the house during cooking with mean concentrations of 9980 ng/m 3 and 18,700 pg/m 3 for PAHs and NPAHs, respectively. The composition profiles of PAHs and NPAHs showed that benz[a]anthracene, benzo[k] fluoranthrene, and benzo[a]pyrene made the greatest contribution to total PAHs, while 9-nitroanthracene made the greatest contribution to total NPAHs. The correlation coefficient (p  <  0.01) of PAHs and NPAHs, using LG as a tracer, confirmed that the main source of PAHs and NPAHs was biomass burning. This was further confirmed by the indoor to outdoor ratios and diagnostic ratios using PAHs and NPAHs and carbonaceous fractions. During cooking periods, the carcinogenic risks exceeded the WHO guideline values and would be classified as “definite risks.” This suggest that biomass burning inside houses poses serious health risks through inhalation, which is the main route of exposure and may increase the incidence of cancer. Upgradation of residential environments is needed to improve indoor air quality, especially, in rural areas of Thailand.